Dengue haemorrhagic fever: questions of pathogenesis. - Cardosa, Mary Jane (Walters Kluwer, 2000)
The year under review has seen a remarkable proliferation of papers on dengue. Four prospective studies have been carried out across the dengue belt, many groups have been pushing at the question of pathogenesis of dengue haemorrhagic fever, and a breakthrough has been achieved in the development of a mouse model for human dengue haemorrhagic fever.